2009
DOI: 10.1089/bfm.2008.0137
|View full text |Cite
|
Sign up to set email alerts
|

Human Milk Adiponectin Is Associated with Infant Growth in Two Independent Cohorts

Abstract: Background: Adiponectin, a circulating adipocyte protein, is associated with lower obesity. We have previously shown that adiponectin is present in human milk. This study determined whether higher milk adiponectin is associated with infant growth and investigated milk adiponectin's oligomeric form. Design and Methods: This is a study of two parallel longitudinal cohorts of breastfed infants born between 1998 and 2005. Forty-five mother-infant pairs from Cincinnati, OH and 277 mother-infant pairs from Mexico Ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
117
3
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(132 citation statements)
references
References 36 publications
10
117
3
2
Order By: Relevance
“…Median levels of adiponectin in our study were substantially lower (by a factor of 2-5) than those reported from women in Italy, Mexico, and the United States (Woo et al 2009;Savino et al 2012). We also observed variation in EGF as a negative function of infant age ( Figure 4B), a result that agrees well with earlier studies (Donovan and Odle 1994).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Median levels of adiponectin in our study were substantially lower (by a factor of 2-5) than those reported from women in Italy, Mexico, and the United States (Woo et al 2009;Savino et al 2012). We also observed variation in EGF as a negative function of infant age ( Figure 4B), a result that agrees well with earlier studies (Donovan and Odle 1994).…”
Section: Discussionsupporting
confidence: 92%
“…In general, lower infant weights and leaner body compositions are associated with higher levels of adiponectin, at least through the first six months of life (Newburg et al 2010; but see Woo et al 2012). The fact that of adiponectin levels in breast milk can fluctuate with maternal energy balance and also in response to preterm or underweight infants suggests that it plays a key role in mediating the adaptive responses of infant adipose tissues (Savino et al 2008(Savino et al , 2010aWoo et al 2009). Adiponectin levels also correlate with linear growth, perhaps because adiponectin activates osteoblasts (Oshima et al 2005).…”
Section: Adiponectinmentioning
confidence: 99%
“…Table 2 below presents the consequences of child growth, according to specific literature. 29,[35][36] Gain in length; gain of weight 23,32,[36][37][38][39][40] Changes on weight and length 29 Gain of weight; relations: weight/age, weight/stature, stature/age 19,35,[41][42][43] Optimum gain of weight 42 High growth 44 Secular acceleration of weight and length 2 Changes in body tissue mass -muscle, fat, and bone 45 Anthropometric measures in patterns of normality 3 Adequate anthropometric indexes according to the child's age and sex established through growth curves 3 Performs general motor skills in accordance with the age pattern 13 Performs refined motor skills in accordance with the age pattern 13 Adequate initial sensorial capacities (touch, taste, smell, sight, hearing, and primitive reflexes) 46 Active and non-structured games increase the child's capacity for controlling movements 12 High Z length/age score [16][17] Duration and quality of sleep 47 High control of parents is decisive for the infants' eating habits 48 Evaluating the consequence "gain of weight" demands the identification of the variables of age, stature, and weight. 19,35,[41][42][43]49 The consequence of child growth "expresses anthropometric measures within the patterns of normality" comprises measures of weight, length, cephalic, and brachial circumferences, triceps, and subscapular skinfold thickness.…”
Section: Resultsmentioning
confidence: 99%
“…Еще одним ограничением являлся нестан-дартизированный отбор проб грудного молока: так, одни исследователи проводили анализ только переднего или заднего молока, а другие -полностью сцеженного из груди молока. Это является принципиально важным, так как концентрация гормонов в грудном молоке может изменяться в течение одного кормления, а также на про-тяжении лактационного периода [42].…”
Section: жировой обменunclassified
“…Тем не менее в отдельных исследованиях установле-но, что аналогично лептину концентрация адипонектина в сыворотке крови матери коррелирует с ее ИМТ [43], а содержание гормона в грудном молоке положительно ПЕДИАТРИЧЕСКАЯ ФАРМАКОЛОГИЯ /2015/ ТОМ 12/ № 1 связано с сывороточными концентрациями как у матери, так и у ребенка [42,43].…”
Section: жировой обменunclassified